Efficacy of a brief psychological intervention for adolescents with recent suicide attempt: A randomized clinical trial - Ainoa García-Fernández; Manuel Couce-Sánchez; Jorge Andreo-Jover; Wala Ayad-Ahmed; María Teresa Bobes Bascarán; Maria Angeles Boti; Manuel Canal Rivero; Ana Isabel Cebriá; Benedicto Crespo-Facorro; Marina Díaz-Marsá; Verónica Fernández-Rodrigues; Sandra Gómez-Vallejo; et al. (European Psychiatry)
Abstract Background Adolescents are at a heightened risk of suicide reattempts following hospital discharge, but few evidence-based interventions exist. This study evaluated the efficacy of the self-awareness of mental health (SAM) program combined with treatment as usual (TAU) versus TAU alone in reducing reattempts among high-risk adolescents.